1994
DOI: 10.1111/j.1365-3083.1994.tb03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 and Interleukin‐6 Receptor are Expressed by Cultured Glomerular Epithelial Cells

Abstract: Interleukin-6 (IL-6) has been extensively studied in mesangial cells but little is known about the expression of this cytokine and its receptor in glomerular epithelial cells (GEC). IL-6 was detected in the culture supernatants of human GEC and its production was enhanced in time and dose dependent manner by lipopolysaccharide (LPS), interleukin-1 beta (IL-1 beta) and tumour necrosis alpha (TNF-alpha). Quiescent, serum-starved GEC did not express clearly IL-6 mRNA. Stimulation of cells with LPS, TNF-alpha or I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Previous investigators have suggested that IL-6 and TNF are produced by human GEC [26, 27, 28]. The current study confirms these observations and provides the new observation that IL-1 is also made by this cell type.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous investigators have suggested that IL-6 and TNF are produced by human GEC [26, 27, 28]. The current study confirms these observations and provides the new observation that IL-1 is also made by this cell type.…”
Section: Discussionsupporting
confidence: 81%
“…To determine if Stx-1-stimulated GEC cytokine production might be modulated by LPS, which is likely present in the serum of patients with HUS, the effect of LPS alone or in combination with Stx-1 was evaluated. LPS alone increased IL-6 and TNF, but not IL-1, production by GEC (while LPS stimulation of IL-6 production by GEC has been described [26], to our knowledge, this is the first report of LPS stimulation of TNF release by this cell type). Notably, LPS stimulation of IL-6 and TNF release occurred in the absence of any apparent cytotoxicity or inhibition of protein synthesis.…”
Section: Discussionmentioning
confidence: 89%
“…We hypothesize that higher urine sIL-6R might originate from the local production of sIL-6R in epithelial cells of the transplant. Activated epithelial cells can most likely secrete sIL-6R, as suggested by culture experiments in which stimulation of glomerular epithelial cells by proinflammatory mediators, such as lipopolysaccharide, increased the expression of IL-6R mRNA (25).…”
Section: Sil-6r Urine Levels In Patients and Healthy Controlsmentioning
confidence: 97%
“…IL-6 is a 26-kDa glycoprotein that is produced by many cell types, such as T and B lymphocytes, fibroblasts, macrophages, and endothelial and epithelial cells (23)(24)(25). IL-6 induces the expression of sIL-6R, a 50-kDa protein that is secreted by human cell lines derived from peripheral blood mononuclear cells, glomerular epithelial cells, osteoblasts, and cells of the central nervous system (24,25). sIL-6R was shown to bind IL-6, thereby prolonging the plasma half life of IL-6 (26).…”
Section: Sil-6r Urine Levels In Patients and Healthy Controlsmentioning
confidence: 99%
“…IL-6 is secreted by different cells, including podocytes, and is a vital modulator of immune and inflammatory responses (3135). IL-6 has been shown to act in a proinflammatory as well as anti-inflammatory manner, and it is thought to act as an immunological switch (36).…”
Section: Introductionmentioning
confidence: 99%